The Ruling of Holding Friday Prayer at Home During COVID-19 Pandemic - Alshehri, Khaled Abdulaziz (Journal of Islamic Sciences, 2020)
This research tries to explain the religion role for people that should pray at home because of COVID- 19 pandemic. The main goal of this research is to understand the religious role of this crisis, and to collect and compare the jurisprudence researchers’ opinions. The research has adopted exploratory and comparative methods, which has resulted in the following results: • Jumma prayer has a special significance that has made it unique in relation to the five obligatory prayers. • The most appropriate religious decision of Jumma prayer is that is it not allowed to be performed in houses but rather mosques, due to that all religious obligatory deeds are fundamental orders. • The differences between jurisprudence researchers about the mosques as the only place of Jumma does not mean it is allowed to do it at home, but they excuse to do it outside mosques, not including houses, with some especial roles.